Hand eczema phototherapy pilot trial. (19th July 2018) - Brass, D.; Fouweather, T.; Stocken, D.D.; Macdonald, C.; Wilkinson, J.; Lloyd, J.; Farr, P.M.; Reynolds, N.J.; Hampton, P.J.
Summary: Hand eczema is one of the most common skin diseases with some studies estimating that up to 10% of the European population has some degree of hand eczema at any one time. There are various causes with some people having a genetic tendency and others developing hand eczema due to their jobs, often a result of hand washing in healthcare or hospitality sectors. The initial treatment of hand eczema is to avoid obvious triggers and use plenty of moisturising creams. If problems continue steroid creams are prescribed. These measures are often enough but if the eczema continues patients are then offered either ultraviolet (UV) light based treatments or tablets. This research study investigated two different forms of UV light treatment which are used to treat eczema. PUVA involves soaking the hands in a water‐based solution of a photosensitising drug before receiving UVA light for 5‐15 minutes whereas NBUVB involves a 1‐2 minute exposure to UVB light. PUVA is the traditional treatment and has been used for 30 years. It is time consuming. There are some concerns that excessive PUVA use could increase the risk of skin cancers and indefinite repeated treatment is not used. The research study invited patients with hand eczema not improving with steroid creams to receive either PUVA or UVB treatment. The severity of their eczema was scored before, during and after treatment. Due to difficulties in recruiting enough patients it was not possible to say which treatment was better. However, the study did show that both treatments improved the eczema severity. There were more side effects with the NBUVB treatment mainly due to mild episodes of skin redness. This research has provided new information. We now know that NBUVB is a safe and acceptable treatment for hand eczema. It does lead to improvement in hand eczema severity. It takes less time but does produce more side effects than PUVA. We have measured the improvement in patients' eczema with both treatments using official scoring systems which means we are now in a position to design a larger clinical trial to determine which treatment is more effective. Abstract : Linked Article:  Brass et al. Br J Dermatol 2018;179 :63–71